STUDY ON ENERGY ABSORPTION CHARACTERISTICS OF COMPOSITE STRUCTURE OF TRUSS SPHERE-FILLED INTERLACED NETWORK TUBE - HUANG PeiGeng; CHEN YaTing; XIONG Yi; HU ZeYuan; LIU WenHao; WU Fei; ZHENG ShiWei; XU MaoDa (Jixie qiangdu)
Absrtact Maxon Cinema 4 D R21 was used to build 3 D model, and the composite structure of truss ball filled interwoven network tube was made by 3 D printing. The uniaxial compression tests of 3 D printed truss ball, aluminum alloy thin-walled tube and composite structure filled with truss ball and interwoven network tube were carried out, and studied the difference between the composite structure of truss-sphere filled interlaced network tube and the other two structures in the energy absorption characteristics. The results show that the deformation degree and energy absorption capacity of the composite structure are directly affected by the impact. The composite structure can bear the highest load and the ball truss can bear the weakest load. The experimental results show that the energy absorption characteristics of the thin-walled tube are between the aluminum alloy thin-walled tube and the truss ball.